Challenges and limitations of validation of the single use medical devices: a review article - Adriana Cristina de Oliveira; Thabata Coaglio Lucas (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
This review study is aimed at analyzing the challenges and limitations of the validation of single use medical device regarding cleaning, sterilization, functional performance and integrity. It was a search in the database LILACS Medline / Pubmed of articles published in the period 2002 to 2007. Eleven articles were analyzed. The findings pointed out that one of the challenges of validation of single use devices was related to conformity of the results of tests and the possibility of reuse. It was verified that the complex physical structures of the materials and the presence of roughness on the surface due to successive reprocessing were factors that hampered the elimination of biofilms, microbial loads and endotoxins. In the evaluation of the functional performance was evidenced a decreased in the performance of the material proportional to the number of reuses. Among the limitations of the validation of single use devices, highlighted the impossibility to extend the results of the studies included for all categories of single use devices.